2022
DOI: 10.3389/fncel.2022.992869
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the integrated stress response reverses oxidative stress damage-induced postoperative cognitive dysfunction

Abstract: Postoperative cognitive dysfunction (POCD) is a common complication following anesthesia and surgery that might lead to a decline in learning and memory. Oxidative stress damage is one of the pathogenic mechanisms underlying POCD. Recent studies had shown that the integrated stress response (ISR) is closely related to oxidative stress. The core response of the ISR is phosphorylation of eIF2α. Various cellular stress stimuli trigger activation of eIF2α kinases, thus causing phosphorylation of eIF2α. ISR is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Hippocampus is a key brain region for the study of spatial memory and episodic memory [ 45 48 ]. Previous studies have demonstrated that spatial memory and hippocampus-dependent memory impairment were found in mice three days after intramedullary fixation of tibial fracture, but hippocampus-independent memory was not affected [ 24 , 25 , 49 ]. Our experiment also proved that the freezing time of mice in the training phase and tone test phase of FC did not show significant statistical difference, but in the context test, the mice in the anesthesia/surgery group showed shorter freezing time.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampus is a key brain region for the study of spatial memory and episodic memory [ 45 48 ]. Previous studies have demonstrated that spatial memory and hippocampus-dependent memory impairment were found in mice three days after intramedullary fixation of tibial fracture, but hippocampus-independent memory was not affected [ 24 , 25 , 49 ]. Our experiment also proved that the freezing time of mice in the training phase and tone test phase of FC did not show significant statistical difference, but in the context test, the mice in the anesthesia/surgery group showed shorter freezing time.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and prolonged neuroinflammation have been considered the main pathological factors contributing to POCD development [ 39 , 60 , 61 , 62 ]. A few studies have suggested that anesthesia and surgery resulted in the increase in malondialdehyde and oxidative damage in the elderly brain and antioxidants could attenuate cognitive dysfunction after anesthesia and surgery [ 45 , 63 , 64 , 65 ]. Moreover, emerging evidence suggested that suppression of neuroinflammation could attenuate cognitive deficits caused by laparotomy and cardiopulmonary bypass surgery under isoflurane anesthesia [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that oxidative stress is an important mechanism in the development of cognitive impairment, which may contribute to cognitive decline [11] . Our previous research also has provided evidence that oxidative stress is involved in the occurrence of POCD, and both the 6h isoflurane anesthesia model and the tibial fracture model have been shown to increase oxidative stress [12,13] . Multiple cellular mechanisms related to oxidative stress have been implicated in the onset of various neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 92%